2008
DOI: 10.6090/jarq.42.163
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Validity and Sensitivity of the DNDC Model for Shimajiri Dark Red Soil

Abstract: The validities of the DeNitrification-DeComposition (DNDC) model and the simulation parameters were examined by using the experimental data obtained at Miyako Branch of Okinawa Prefectural Agricultural Research Center. The obtained simulation results were compared with the observed values and it was concluded that the simulation with the measured parameters could produce better simulation results than the simulation with the model provided default parameters. The model seemed to be able to predict the total am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Nevertheless, in 2006 the DNDC model predictions showed a better match of the simulated soil temperatures to the measured data compared to those obtained by the SWAP model. As shown by Nakagawa et al (2008), the DNDC model demonstrated high sensitivity to air temperatures as well as a satisfactory efficiency in predicting soil temperatures at the depths of 15 and 35 cm.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, in 2006 the DNDC model predictions showed a better match of the simulated soil temperatures to the measured data compared to those obtained by the SWAP model. As shown by Nakagawa et al (2008), the DNDC model demonstrated high sensitivity to air temperatures as well as a satisfactory efficiency in predicting soil temperatures at the depths of 15 and 35 cm.…”
Section: Resultsmentioning
confidence: 97%
“…However, the results of Jiang et al (2011) showed that the SWAP model could overestimate the soil water content at the depth of 15 cm and predict it efficiently at the depths of 35, 65, and 95 cm. Nakagawa et al (2008) reported that the DNDC model overestimated the soil water content but produced a better efficiency if the measured input parameters were used instead of default ones. The Nash-Sutcliffe efficiency (E) coefficients supported the results of the statistical analysis of the RMSE values.…”
Section: Resultsmentioning
confidence: 99%
“…According to the study conducted by Nakagawa et al [28], a total amount of 63.6 kg N/ha was leached as nitrate-N from their sugarcane-cultivated lysimeter unit, and they observed large increases in leached nitrate amounts during periods of typhoons and heavy rains [28]. In addition, Shuhei [29] reported that the trend in the concentration of nitrate-N at the springs on Miyako Island was only matched with that of N emission from chemical fertilizer and inferred that GW was predominantly affected by chemical fertilizers.…”
Section: Introductionmentioning
confidence: 99%